Influence of the ICT learning model on quality improvement at Mandiri LPK SNU’R Bogor - Iwan Armawan; Amiruddin Saleh; Pudji Muljono; Musa Hubeis (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
One way to improve the quality of learning is by increasing the relevance of the teaching model. The teaching model is said to be relevant if in the process it can deliver students achieve educational goals with relevant models according to their needs. A training and course institution (LPK) is a form of non-formal education unit organized for people who need knowledge, skills, and attitudes to develop themselves. The main study was carried out on LPK Mandiri Snur located in Bogor, West Java, regarding the effect of the information communication technology (ICT) learning model on improving the quality of the training and skills aspects carried out by LPK so that they can compete in the industrial world. In particular, the problems studied and analyzed and the purpose of this research is to analyze the use of ICT in influencing the learning model and analyze the influence of the ICT learning model on the quality of learning at LPK Mandiri Snur Bogor. The research design uses a mixed method approach combining quantitative research approaches and qualitative research approaches. The approach begins with implementation, planning, data collection, hypotheses, data analyzers, and interpreters. Based on the analysis test, it is known that the ICT learning model has a significant effect on quality. The results of the learning model of the use of ICT for quality present similar conditions for online, offline, and blended learning. The influence of the ICT learning model gets several results in quality, namely increasing student skills, changing attitudes, awareness, and abilities of students' human resources in using ICT, human resource development has a significant effect on the quality of learning at LPK Mandiri Snur Bogor.